The Current Status and Prospects of the Application of Digital Technology in the Field of Pharmacovigilance of Rare Diseases - CAO Ying; LIU Xinru; WANG Shengfeng; ZHUO Lin (罕见病研究)
Objective To summarize the current status in the application of digital and intelligent technologies in the field of pharmacovigilance and to provide reference to the selection and development of methods for pharmacovigilance of rare diseases. Methods Searched five major databases-CNKI, WANFANG, VIP, PubMed, and Embase, selected and the data of application of digital technology in the field of drug vigilance for rare diseases, extracted relevant information and conducted a systematic review. Results The application of digital technology in drug surveillance has not yet been used in the special field of rare diseases. Relevant case studies are insufficient. Two major challenges need to be addressed. One is the insufficient data sources and the other is technical limitations. Conclusions Based on the characteristics of drugs for rare diseases, this paper identifies data sources and intelligent technologies suitable for the field of drug vigilance for rare disease, proposes direction for potential development in the future, and makes targeted suggestions.